Egypt Land : Race and Nineteenth-Century American Egyptomania - Trafton, Scott, 1968- (Book collections on Project MUSE., 2004)
Explores the relation between nineteenth-century American interest in ancient Egypt in architecture, literature, and science, and the ways Egypt was deployed by advocates for slavery and by African American writers.